Calculation of the Vertical Velocity in the Asian Summer Monsoon Anticyclone Region Using the Thermodynamic Method With in situ and Satellite Data - Guo, Dong; Shen, Peijie; Shi, Chunhua; Wang, Meirong; Liu, Yu; Zhang, Chenxin; Li, Wenwen (Frontiers in Earth Science, 2020)
The correct calculation of the vertical velocity of the Asian Summer Monsoon anticyclone (ASMA) region is helpful to know more accurately the ozone stratosphere-troposphere exchange, so as to explore the variation of ozone in the ASMA region. Therefore, the vertical velocity over the ASMA in June, July, August and September 2012 and 2016 is calculated by the thermodynamic method, which may avoid the deviations from the kinematics method using the mass continuity equation. In order to improve the accuracy, we used high-resolution heating rate datasets obtained via the Beijing Climate Center Radiation Transfer Model based on in situ observations and revised satellite data from MLS/AIRS. The vertical velocity calculated by the thermodynamic method (VT) is then compared with the data from ERA-Interim (VERA-I). In the daytime, values of VT were similar to VERA-I, and were dominated by ascending motion, although VT showed descending motion at the western edge of the ASMA below 100 hPa. The intensity of VT was slightly smaller than that of VERA-I at lower levels (200 hPa –100 hPa) over the ASMA region and significantly weaker above 100 hPa. In the night-time, situation was more complex. Both VT and VERA-I showed the convergence of vertical wind at 150 hPa, and the divergence at 80 hPa, but VT had a smaller standard deviation. Besides, VT showed descending in the western and northern ASMA, but VERA-I only descended in the west. The descending motion in the west, seen in both VT and VERA-I, is produced by the heating difference between Qinghai-Tibet Plateau and Iranian Plateau. The difference of the two vertical velocities in the northern ASMA may indicate the different understandings of the local Hadley Circulation and local Brewer-Dobson Circulation.